Fungal endocarditis after transcatheter aortic valve implantation complicated with pseudoaneurysm of the ascending aorta - Luciano Moreira Baracioli; Walberto Monteiro Neiva Eulálio Filho; Rinaldo Focaccia Siciliano; André Franci; Giorgio Marinaro; Roberta Saretta; Ramez Anbar; Fabio Biscegli Jatene (Journal of Cardiothoracic Surgery)
Abstract Fungal endocarditis following transcatheter aortic valve implantation (TAVI) is a rare and serious complication of this procedure. We describe a case of a 75-year-old patient who developed fungal endocarditis caused by Candida albicans, complicated by an aortic pseudoaneurysm.